2021
DOI: 10.3390/nu13010240
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Cognitive and Behavioural Effects of Maternal Obesity

Abstract: The widespread consumption of ‘western’-style diets along with sedentary lifestyles has led to a global epidemic of obesity. Epidemiological, clinical and preclinical evidence suggests that maternal obesity, overnutrition and unhealthy dietary patterns programs have lasting adverse effects on the physical and mental health of offspring. We review currently available preclinical and clinical evidence and summarise possible underlying neurobiological mechanisms by which maternal overnutrition may perturb offspri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 132 publications
2
32
1
Order By: Relevance
“…These observations chime with the Developmental Origins of Health and Disease—framework of chronic illnesses, according to which prenatal adversity leads to permanent changes in the development of organs, cells, and body’s biological feedback mechanisms, thereby contributing to an increased risk of chronic illnesses, including mental disorders subsequently 38 . Supporting the DOHaD framework and the possible role of under-or overnutrition underlying our findings, previous studies have shown that maternal undernutrition during pregnancy due to famine exposure may predict the risks of several different mental disorders in the offspring 3 , 26 , 27 , 29 , that specific maternal dietary patterns may predict increased risks of psychiatric symptoms and suboptimal neurodevelopment in children 25 , and that maternal obesity, dietary patterns and undernutrition in pregnancy may each predict altered brain structure in the offspring 3 , 25 , 39 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These observations chime with the Developmental Origins of Health and Disease—framework of chronic illnesses, according to which prenatal adversity leads to permanent changes in the development of organs, cells, and body’s biological feedback mechanisms, thereby contributing to an increased risk of chronic illnesses, including mental disorders subsequently 38 . Supporting the DOHaD framework and the possible role of under-or overnutrition underlying our findings, previous studies have shown that maternal undernutrition during pregnancy due to famine exposure may predict the risks of several different mental disorders in the offspring 3 , 26 , 27 , 29 , that specific maternal dietary patterns may predict increased risks of psychiatric symptoms and suboptimal neurodevelopment in children 25 , and that maternal obesity, dietary patterns and undernutrition in pregnancy may each predict altered brain structure in the offspring 3 , 25 , 39 .…”
Section: Discussionsupporting
confidence: 84%
“…Neurobiologically, inflammatory pathways and other mechanisms related to individual’s altered stress vulnerability because of maternal obesity or underweight may have contributed to our findings. Obesity in pregnancy is a highly proinflammatory state 4 , 17 , 25 , 51 , and prenatal inflammation has been associated with psychopathology risk in the offspring 17 , 52 , 53 . Maternal BMI in pregnancy has been associated with altered functioning of the hypothalamus-pituitary adrenal axis in the offspring 54 , and changes in the functioning of this axis are characteristic of patients with mental disorders 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While meta-analytic evidence suggests that obesogenic diets increase anxiety-like behaviour in the EPM and OFT in rodents consuming such a diet [60], here, we found anxiolytic effects of maternal Caf diet exposure in young offspring, regardless of whether these offspring were themselves fed a chow or Caf diet. Altered maternal care by Caf dams, maternal obesity-induced changes to offspring brain development, inflammatory changes, and maternal transfer of gut microbiota are among the mechanisms that may mediate behavioural changes in offspring [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that maternal obesity may also confer risk of behavioural changes in offspring [24]. A meta-analysis found that children of mothers with obesity, relative to those of normal weight, had 60% higher rates of neurodevelopmental disorders including autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) [25].…”
Section: Introductionmentioning
confidence: 99%